Pomalidomide Reduces Ischemic Brain Injury in Rodents. Issue 4 (April 2019) - Tsai, Yan-Rou; Tweedie, David; Navas-Enamorado, Ignacio; Scerba, Michael T.; Chang, Cheng-Fu; Lai, Jing-Huei; Wu, John Chung-Che; Chen, Yen-Hua; Kang, Shuo-Jhen; Hoffer, Barry J.; de Cabo, Rafael; Greig, Nigel H.; et al.
Stroke is a leading cause of death and severe disability worldwide. After cerebral ischemia, inflammation plays a central role in the development of permanent neurological damage. Reactive oxygen species (ROS) are involved in the mechanism of post-ischemic inflammation. The activation of several inflammatory enzymes produces ROS, which subsequently suppress mitochondrial activity, leading to further tissue damage. Pomalidomide (POM) is a clinically available immunomodulatory and anti-inflammatory agent. Prior cellular studies demonstrate that POM can mitigate oxidative stress and lower levels of pro-inflammatory cytokines, particularly TNF-α, which plays a prominent role in ischemic stroke-induced brain damage and functional deficits. To evaluate the potential value of POM in cerebral ischemia, POM was initially administered to transgenic mice chronically over-expressing TNF-α surfactant protein (SP)-C promoter (SP-C/TNF-α mice) to assess whether systemically administered drug could lower systemic TNF-α level. POM significantly lowered serum levels of TNF-α and IL-5. Pharmacokinetic studies were then undertaken in mice to evaluate brain POM levels following systemic drug administration. POM possessed a brain/plasma concentration ratio of 0.71. Finally, rats were subjected to transient middle cerebral artery occlusion (MCAo) for 60 min, and subsequently treated with POM 30 min thereafter to evaluate action on cerebral ischemia. POM reduced the cerebral infarct volume in MCAo-challenged rats and improved motor activity, as evaluated by the elevated body swing test. POM's neuroprotective actions on ischemic injury represent a potential therapeutic approach for ischemic brain damage and related disorders, and warrant further evaluation.